The Gods of The People of Noah in The Religious Texts Study in the linguistic Origin in Sumerian History. [In Arabic] - Adil Hashim Ali (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2019)
The holy Quran has been not had enough studies in Archaeology and ancient languages to get more understanding. The Quran historical event needs in necessary to widely vision for this event,and with other cultural tools like ancient languages we could understand the word and text in Quran in particular the word which belong to old or ancient event as well as a historical study for the period of event. According to this methodology, the research deal with qur'anic text (Ayah) in style of (Tedabur) as attempt to understand the significance of the names of the gods of the people of Noah (Sumerians)  and rooting this names to Mesopotamian languages. The name of Gods are contained in Surat Noah.